The role of host pigments in coral photobiology - Ferreira, Gabriel; Bollati, Elena; Kühl, Michael (Frontiers in Marine Science, 2023)
Corals have the ability to synthesize various pigments, responsible for their characteristic vivid coloration. Most coral host pigments are green fluorescent protein (GFP)-like pigments exhibiting diverse spectral properties covering almost the entire visible spectrum, with pigments fluorescing from cyan to red. The type of pigment a coral can synthesize varies inter- and intraspecifically. However, the precise role of host pigments in coral biology has not been fully elucidated. Host pigments have the ability to modify local light fields and could thus contribute to optimizing the light exposure of the photosymbionts. Such fine-tuning of the light microenvironment could enable the holobiont to adapt to broader environmental conditions. Putative mechanisms include energy transfer between host pigments, as well as modulation of their scattering properties via tissue plasticity and granule formation that affect the distribution and organization of host pigments in coral tissue. These mechanisms can enable either photoprotection or photoenhancement depending on the coral’s environment. In this review, we summarize and discuss current knowledge about the link between host pigments and symbiont photosynthesis in reef-building corals, and discuss limitations and challenges of experimental investigation of this connection.